2004
DOI: 10.1021/nl048654j
|View full text |Cite
|
Sign up to set email alerts
|

Probing Single DNA Molecule Transport Using Fabricated Nanopores

Abstract: Nanopores can serve as high throughput, single-molecule sensing devices that provide insight into the distribution of static and dynamic molecular activities, properties, or interactions. We have studied double stranded DNA electrophoretic transport dynamics through fabricated nanopores in silicon nitride. A fabricated pore enables us to interrogate a broader range of molecules with a wider range of conditions than can be investigated in a self-assembled protein pore in a lipid membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
361
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(403 citation statements)
references
References 31 publications
39
361
2
1
Order By: Relevance
“…This implies that molecules test multiple configurations prior to capture, which is a statistical process governed by energetic considerations. By contrast, Chen et al reported a bias for unfolded translocations that increased with applied voltage [5]. This finding implies that molecules pre-align in the fields outside the pore rather than sample multiple configurations prior to capture.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This implies that molecules test multiple configurations prior to capture, which is a statistical process governed by energetic considerations. By contrast, Chen et al reported a bias for unfolded translocations that increased with applied voltage [5]. This finding implies that molecules pre-align in the fields outside the pore rather than sample multiple configurations prior to capture.…”
mentioning
confidence: 90%
“…The capture location, x ≡ Ls Ls+L l , is the fractional contour distance from the initial fold to the nearest end. The time for each segment to translocate is measurable from the time trace of I [4][5][6] and can be used to estimate x. Storm et al inferred the distribution of x for λ DNA translocations and concluded that folds occur with equal probability everywhere along a molecule's length, but that the DNA is more likely to be captured at its ends because of the lower energetic cost of threading an unfolded molecule [6].…”
mentioning
confidence: 99%
“…These authors detected the translocation of the PN via measurement of the blockade current, discussed below. Since this pioneering experiment, nanopores have been used to extract a variety of information characterizing the translocation, dynamics, and interactions of both single-and double-stranded PNs in nanopores ͑Kasianowicz et Akeson et al, 1999;Henrickson et al, 2000;Meller et al, 2000Meller et al, , 2001Deamer and Branton, 2002;Chang et al, 2004;Chen et al, 2004;Fologea, Gershow, Ledden, et al, 2005;Mathé et al, 2005;Butler et al, 2006͒. Further 2003; Wanunu and Meller, 2007͒.…”
Section: Nanopores and Polynucleotidesmentioning
confidence: 99%
“…In recent years, SAMs found wide applications in chemistry, physics, and especial biology [2][3][4][5] when SAMs combined with microfluidic technology [6][7][8][9][10]; for example, we applied alkanethiolate SAMs on gold surface to study the relationship between the shape of mammalian cells and their migration direction [11]. Recently, when we applied alkanethiolate SAMs combined with microfluidic technology to establish interaction models for multiple types of cells [12], we found that the SAMs diffused on the surfaces of evaporation-coated gold slides which were covered with polydimethylsiloxan (PDMS) stamps [13].…”
Section: Introductionmentioning
confidence: 99%